Financial consolidation and liquidity: prudential regulation and/or competition policy? - Patrick Van Cayseele (National Bank of Belgium, 2004)
A model of loan rate competition with liquidity provision by banks is used to study bank mergers. Both loan rate competition and liquidity needs are seen to be "localised" phenomena. This allows for tracing down the effects of particular types of bank mergers. As such, we contrast the effects of "revenue base enhancing" mergers with the effects of mergers "for market power". The optimal post merger loan rate and risk management decisions are derived. The fundamental trade-off between stability and efficiency is often present, indicating that the approval of bank mergers induces difficult policy choices.
Keywords: D43; G21; L40; G28; 330; bank mergers; merger review process; liquidity; loan Rates; Bank; Unternehmenskonzentration; Kreditpolitik; Wettbewerb; Bankenliquidität; Theorie